Identification, Cloning, and Characterization of l-Phenylserine Dehydrogenase from Pseudomonas syringae NK-15. (25th March 2010) - Ueshima, Sakuko; Muramatsu, Hisashi; Nakajima, Takanori; Yamamoto, Hiroaki; Kato, Shin-ichiro; Misono, Haruo; Nagata, Shinji
Abstract : The gene encodingd -phenylserine dehydrogenase from Pseudomonas syringae NK-15 was identified, and a 9, 246-bp nucleotide sequence containing the gene was sequenced. Six ORFs were confirmed in the sequenced region, four of which were predicted to form an operon. A homology search of each ORF predicted that orf3 encodedl -phenylserine dehydrogenase. Hence, orf3 was cloned and overexpressed in Escherichia coli cells and recombinant ORF3 was purified to homogeneity and characterized. The purified ORF3 enzyme showedl -phenylserine dehydrogenase activity. The enzymological properties and primary structure ofl -phenylserine dehydrogenase (ORF3) were quite different from those ofd -phenylserine dehydrogenase previously reported.l -Phenylserine dehydrogenase catalyzed theNAD + -dependent oxidation of theβ -hydroxyl group ofl -β -phenylserine.l -Phenylserine andl - threo -(2-thienyl)serine were good substrates forl -phenylserine dehydrogenase. The genes encodingl -phenylserine dehydrogenase andd -phenylserine dehydrogenase, which is induced by phenylserine, are located in a single operon. The reaction products of both enzymatic reactions were 2-aminoacetophenone andCO 2 .